Molecular Pathogenesis of Intrahepatic Cholestasis of Pregnancy - Jianping Xiao; Zeying Li; Yutong Song; Yujie Sun; Hanfei Shi; Daozhen Chen; Yan Zhang (Canadian Journal of Gastroenterology and Hepatology)
Intrahepatic cholestasis of pregnancy (ICP) is a pregnancy-specific liver disease. The maternal symptoms are characterized by skin pruritus and elevated bile acids, causing several adverse outcomes for fetuses, including an increased risk of preterm birth, meconium-stained amniotic fluid, neonatal depression, respiratory distress syndrome, and stillbirth. Genetic, hormonal, immunological, and environmental factors contribute to the pathogenesis of ICP, and the estrogen-bile acid axis is thought to play a dominant role. The advances in the past 10 years uncover more details of this axis. Moreover, dysregulation of extracellular matrix and oxygen supply, organelle dysfunction, and epigenetic changes are also found to cause ICP, illuminating more potential drug targets for interfering with. Here, we summarize the molecular pathogenesis of ICP with an emphasis on the advancement in the past 10 years, aiming to give an updated full view of this field.